PENGARUH PENGGUNAAN MODEL EXPERIENTIAL LEARNING TERHADAP KEMAMPUAN SISWA MENULIS TEKS PUISI PADA MAHASISWA KEPERAWATAN INSTITUT KESEHATAN DELI HUSADA DELI TUA - Gurusinga, Mona Fitri (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2021)
Writing skill is a skill that is more complex than other skills. Writing is a skill that is done indirectly develop creativity, courage and confidence.This activity provides many benefits to students. The aims of the study to determine the effect of using the experiential learning model on the ability to write text in nursing students of the Health Institute the DELI HUSADA Deli Tua 2019/2020.The sample of this research is one class of 40 students selected by cluster sampling. The data collection technique used was in the form of assignment questions carried out in the pretest and posttest. The data analysis technique used is the normality test using the F test, homogeneity test and hypothesis testing using the t test. The hypothesis in this study was tested with the t test at the significant level Î± = 0.05. From the calculation data, it was obtained that the average of the pretest was 56.85 and the average of the posttest was 77.25, tcount> ttable (10.680> 2.02439). the hypothesis is null that H0 is rejected and Ha is accepted. With the research results, can be concluded that the Experiential Learning Model can improve student learning outcomes in writing poetry texts.